Correlation between the length of the ski track and the velocity of top slalom skiers - Zvan, M.; Lesnik, B. (Acta Universitatis Palackianae Olomucensis. Gymnica, 2007)
Theoretically, the shortest possible line of skiing (ski track) is the best one. But in practice it is very difficult to carry this out and besides it is very risky. It can therefore be only a part of the tactics of the best competitors. With the help of a kinematic analysis, differences in the choice of a line of skiing between individual competitors were established based on a sample of top competitors in the World Cup in Kranjska Gora. We tried to establish whether the competitors achieved higher velocities with such a line of skiing, thus achieving faster sliding among the slalom gates and in the end a better time. In the first part of our research it was proven that none of the competitors had an extremely short line of skiing in the first two successive turns. It was also found out that the competitors who had the shortest lines of skiing in the first analysed turn had, as a rule, the longest lines of skiing in the second turn and vice versa. Based on these findings, it could be claimed that under present conditions, it is extremely difficult, possibly even impossible, to ski in such a way that the line of skiing would be very short in several successive turns. The second part of our research focussed on the establishment of the correlation between the trajectories of the skis and the velocity of skiing. The calculations of the correlations proved a statistically significant correlation between the average velocity of skiing and an average distance of the length of the line of skiing from the y-axis in the entire measured segment. It was established that the measured space was covered faster by the competitors whose line of skiing was shorter, which means more direct.